A Canine Conundrum, or What Would Elvis Do?. (1st March 2016) - Maltenfort, Michael
Summary: The dog Elvis became famous by finding optimal paths that solve various calculus problems. Not all problems, however, have solutions. By giving an unsolvable problem very similar to those Elvis solved, we provide a reminder that it is necessary to prove, rather than assume, that optimal paths exist.